The influence of utilitarian value, hedonic value, social value, and perceived risk on customer satisfaction: Survey of e-commerce customers in Indonesia - Tri Yulistyawati Evelina; Andriani Kusumawati; Umar Nimran; Sunarti (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The purpose of this study is to build an understanding of the influence of utilitarian value, hedonic value, social value, and perceived risk on e-commerce customer satisfaction in Indonesia. Data was collected through an online survey and analyzed using Structural Equation Modeling (SEM) with the WarpPLS tool version 6.0 which was then analyzed through Inferential Statistics analysis. The results of the study showed that utilitarian value significantly influences customer satisfaction. Hedonic value significantly influences customer satisfaction. However, the findings showed that social value did not have a significant effect on customer satisfaction, meaning that the level of the social value of e-commerce customers does not have a significant impact on the level of customer satisfaction. Finally, the results show, perceived risk significantly influences customer satisfaction.
Keywords: M31; 650; utilitarian value; hedonic value; social value; perceived risk; customer satisfaction; e-commerce